THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND TIME MANAGEMENT ON THE SUCCESS OF MEMORIZING THE QUR'AN - Iqomatin, Durrotul; Lina (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2023)
This research aimed to determine the existence of a positive and significant relationship between the level of emotional intelligence and time management and the success of memorizing the Qur'an and to find out how much influence it has on tahfiz students at Islamic Boarding School Bantul Yogyakarta An Nur (Al-Maghfiroh Complex). The research subjects were Islamic boarding school students at Madrasah Aliyah level, with a total of 78 students. Data collection used questionnaire methods and test methods. Instrument content validity analysis was carried out using the Aiken formula, while reliability estimation used Cronbach Alpha. Data analysis was carried out using multiple regression analysis. The results of this research showed that the variables emotional intelligence (X1) and time management (X2) had a strong, positive, and significant relationship with the success of memorizing the Qur'an. It was proven by correlation values (r) of 0.656 and 0.212. Together, the variables emotional intelligence (X1) and time management (X2) influence the success of memorizing the Qur’an (Y) by 54.5%. As for the remaining 45.5%, success in memorizing the Qur’an was influenced by other variables not explained in this research. Therefore, this research could contribute to students memorizing the Qur'an, thereby influencing their intelligence and the time management they carried out in the future learning process.